Modelling uncertainty in the relative risk of exposure to the SARS-CoV-2 virus by airborne aerosol transmission in well mixed indoor air. (15th March 2021) - Jones, Benjamin; Sharpe, Patrick; Iddon, Christopher; Hathway, E. Abigail; Noakes, Catherine J.; Fitzgerald, Shaun
Abstract: We present a mathematical model and a statistical framework to estimate uncertainty in the number of SARS-CoV-2 genome copies deposited in the respiratory tract of a susceptible person, ∑ n, over time in a well mixed indoor space. By relating the predicted median ∑ n for a reference scenario to other locations, a Relative Exposure Index (REI) is established that reduces the need to understand the infection dose probability but is nevertheless a function of space volume, viral emission rate, exposure time, occupant respiratory activity, and room ventilation. A 7  h day in a UK school classroom is used as a reference scenario because its geometry, building services, and occupancy have uniformity and are regulated. The REI is used to highlight types of indoor space, respiratory activity, ventilation provision and other factors that increase the likelihood of far field ( > 2  m) exposure. The classroom reference scenario and an 8  h day in a 20 person office both have an REI ≃ 1 and so are a suitable for comparison with other scenarios. A poorly ventilated classroom (1.2 l s −1  per person) has REI > 2 suggesting that ventilation should be monitored in classrooms to minimise far field aerosol exposure risk. Scenarios involving high aerobic activities or singing have REI > 1 ; a 1  h gym visit has a median REI = 1 . 4, and the Skagit Choir superspreading event has REI > 12 . Spaces with occupancy activities and exposure times comparable to those of the reference scenario must preserve the reference scenario volume flow rate as a minimum rate to achieve REI = 1, irrespective of the number of occupants present. Highlights: A model to evaluate exposure to SARS-CoV-2 in well-mixed indoor spaces. A comparison of the relative exposure risk of common indoor scenarios. Highlights factors that increase exposure. Identifies the need for a minimum airflow rate.